The Role of Digital Transformation in Improving Medical Center Management Efficiency: Primary Healthcare Centers in Northern Syria as a Model - Hlaak, Hussam Ahmad; Aleid, Ali Alhousain; Al-Huseyin, Attia (Arab Journal for Sciences and Research Publishing, 2025)
This study aimed to analyze the role of digital transformation in improving the efficiency of medical center management, with a practical application on primary healthcare centers in northern Syria. It also aimed to make effective contributions to improving healthcare through technical innovation and digital transformation, and to provide recommendations and suggestions for improving the implementation of digital transformation in medical centers. To achieve the study's objectives and discuss its questions, a descriptive analytical approach was adopted. A questionnaire was used to collect the required information. A sample of (70) employees and administrators working in primary healthcare centers affiliated with the Independent Doctors Organization - Eastern Office was selected. The study reached a number of results, the most important of which are: The availability of digital transformation dimensions in primary healthcare centers affiliated with the Independent Doctors Organization is at a good level. In addition, there is a positive relationship between digital transformation and the efficiency of medical center management in primary healthcare centers affiliated with the Independent Doctors Organization. The study also concluded that (communication networks, devices and equipment, and software) as dimensions of digital transformation affect the efficiency of medical center management, while the variable (governance for digitization) does not affect the efficiency of medical center management. Accordingly, the study recommended the need to provide all the requirements for a successful digital transformation and ensure a genuine desire on the part of senior management and officials within organizations. Additionally, it recommended providing full financial and organizational support, developing and motivating individuals through training and providing financial support in the field of digital transformation.
Keywords: Digital transformation; governance; communication networks; software; medical center management efficiency